Catalyst structure, device and method for preparing synthesis gas
By using materials such as silicon carbide or silicon nitride as the catalyst structure of the substrate, combined with metal oxide support and active particles, the problems of vulnerability to existing catalysts and low thermal conductivity are solved, and more efficient heat transfer and long-term durability are achieved.
Patent Information
- Application Number
- CN202311726331.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-08-24
- Filing Date
- 2023-12-14
- Publication Date
- 2025-02-25
AI Technical Summary
The existing catalysts are prone to damage during the reforming reaction, resulting in increased flow resistance and deterioration in performance, and the low thermal conductivity of the alumina catalyst leads to temperature gradients and coke formation.
Using a catalyst structure consisting of silicon carbide, silicon nitride or a composite thereof as the substrate, by arranging metal oxide support and metal active particles on the partition wall of the substrate, heat transfer performance is improved and pressure loss is reduced.
The heat transfer performance in the catalyst layer is improved, the temperature gradient and flow resistance are reduced, the durability of the catalyst is extended, and the efficiency of the reforming reaction is improved.
Smart Images

Figure CN119500210A_ABST
Abstract
Description
[0001] Related Applications
[0002] This application claims priority to and the benefit of Korean Patent Application No. 10-2023-0111502 filed in the Korean Intellectual Property Office on August 24, 2023, the entire contents of which are incorporated herein by reference. Technical Field
[0003] The present disclosure relates to a catalyst structure for preparing synthesis gas, an apparatus for preparing synthesis gas including the catalyst structure, and a method for preparing synthesis gas using the catalyst structure. Background Art
[0004] Gas containing hydrogen and carbon monoxide is a very important substance for supplying hydrogen used in fuel cells in the automotive industry, reducing iron ore in the steel industry, synthesizing ammonia, methanol, Fischer-Tropsch in the chemical industry, and preparing other chemicals.
[0005] To produce this gas, synthesis gas is produced from hydrocarbons by a reforming process, in which a catalyst of a nickel-based alumina or ruthenium-based alumina component is mainly used.
[0006] In conventional reforming methods, pellet-type catalysts are filled into reactors. However, pellet-type catalysts can be damaged into fragments. When loaded into the reactor, the pellet-type catalysts can be damaged due to mechanical shocks when thermal expansion and contraction occurs during shutdown after the reaction by heating to the reforming reaction temperature (about 600°C or higher), or when coke is produced. The small pellet fragments produced by these phenomena fill the gaps between the catalyst pellets and at the bottom of the reactor, thereby causing flow resistance to the reaction gas. In addition, pellets made of alumina have low thermal conductivity and form a temperature gradient within the reactor, causing catalyst performance degradation and coke formation. Summary of the invention
[0007] One aspect of the present disclosure provides a catalyst structure for preparing synthesis gas, which can improve the temperature gradient within the catalyst layer by improving the heat transfer performance, reduce the pressure loss within the catalyst layer and the flow resistance of the reaction gas, and achieve excellent long-term durability.
[0008] According to one aspect, a catalyst for preparing synthesis gas comprises: a substrate (substrate, substrate, substrate), comprising a flow path separated by a partition wall; and a catalytic material, arranged on the surface of the partition wall of the substrate and comprising a metal oxide carrier and metal active particles supported on the metal oxide carrier, wherein the substrate comprises silicon carbide (SiC), silicon nitride (Si 3 N 4 ), metal silicon (Si)-silicon carbide (SiC) composites, metal silicon (Si)-silicon nitride (Si3 N 4 )complex or a combination thereof.
[0009] The catalytic material may be coated on the inner walls of the flow paths of the substrate.
[0010] The substrate may have a honeycomb shape or an integral shape (monolithic shape).
[0011] The catalyst structure may have a thermal conductivity of 10 W / mK or greater.
[0012] The partition wall of the substrate may have a plurality of holes.
[0013] The partition walls of the substrate may have a porosity ranging from 10% to 80%.
[0014] The catalytic material may be included in an amount ranging from 20 g to 300 g per 1 L volume of the catalyst structure.
[0015] The metal active particles may include nickel (Ni), cobalt (Co), rhodium (Rh), ruthenium (Ru), iridium (Ir), palladium (Pd), platinum (Pt), gold (Au), iron (Fe), alloys thereof, or combinations thereof.
[0016] The metal oxide support may include alumina (Al 2 O 3 ), silicon dioxide (SiO 2 ), magnesium oxide (MgO), magnesium aluminate (MgAl 2 O 4 ), zirconium oxide (ZrO 2 ), cerium dioxide (CeO 2 ), lanthanum oxide (lantana) (La 2 O 3 ), yttrium oxide (Y 2 O 3 ) or a combination thereof.
[0017] The metal active particles may be included in an amount ranging from 5 wt % to 30 wt % based on the total weight of the catalytic material.
[0018] According to another aspect, an apparatus for preparing synthesis gas comprises a reactor tube (reactor tube) comprising the above-mentioned catalyst structure for generating synthesis gas.
[0019] The flow paths of the catalyst structures may be arranged along the longitudinal direction (longitudinal direction) of the reactor tube.
[0020] The reactant gases may be configured to pass through the channels of the catalyst structure.
[0021] The catalyst structure may be in direct contact with the inner wall of the reactor tube.
[0022] The reaction gas may be configured not to pass between the catalyst structure and the inner wall of the reactor tube.
[0023] According to another aspect, a method for preparing synthesis gas includes injecting a reaction gas and an oxidant into a flow path of the catalyst structure for preparing synthesis gas. The method further includes reforming the reaction gas through an endothermic reaction to prepare the synthesis gas.
[0024] The reaction gas may include C1 to C20 alkanes, C1 to C20 alkenes, C1 to C20 alkynes, ammonia (NH 3 ), formaldehyde (HCOH), methanol (CH 3 OH) or a combination thereof.
[0025] The oxidant may include carbon dioxide (CO 2 )、Steam(H 2 O), oxygen (O 2 ) or a combination thereof.
[0026] According to an embodiment, the catalyst structure for preparing synthesis gas can ensure improved heat transfer performance to reduce the temperature gradient in the catalyst layer to improve catalyst performance, reduce the pressure loss within the catalyst layer and the flow resistance of the reaction gas, and inhibit the sintering of active metals in the catalyst to achieve long-term durability. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 is a perspective view schematically showing a catalyst structure for preparing synthesis gas according to an embodiment.
[0028] Figure 2 is perpendicular to Figure 1 2 is a cross-sectional view taken in the longitudinal direction of the flow path, and is an enlarged cross-sectional view showing the flow path in an enlarged manner.
[0029] Figure 3 is a graph showing the results of evaluating the reforming performance of the catalyst structures prepared in Example 1 and Comparative Examples 1 to 3.
[0030] Figure 4 Graph showing the results of evaluating the reforming performance of the catalyst structures prepared in Example 1, Example 6 and Comparative Example 3.
[0031] Figure 5 is a schematic diagram showing the results of evaluating the reforming performance of the catalyst structures prepared in Examples 1 to 4.
[0032] Figure 6 is a schematic diagram showing the results of evaluating the reforming performance of the catalyst structures prepared in Examples 1 and 5.
[0033] Figure 7 is a schematic diagram showing the results of evaluating the reforming performance of the catalyst structures prepared in Example 1 and Examples 7 to 9.
[0034] Description of Reference Numerals
[0035] 2. Substrate
[0036] 4 Cylindrical outer surface
[0037] 6 Upstream
[0038] 8 Downstream end
[0039] 10 Flow Path
[0040] 12 Divider Wall
[0041] 14 Catalytic materials. DETAILED DESCRIPTION
[0042] By referring to the following description of the embodiments with reference to the accompanying drawings, the advantages, features and aspects described below will become apparent. However, the embodiments should not be construed as being limited to the embodiments described herein. Although not particularly limited, all terms including technical terms and scientific terms used herein have meanings understood by those skilled in the art. Unless clearly defined, terms defined in commonly used dictionaries should not be interpreted ideally or exaggeratedly.
[0043] In addition, unless explicitly described to the contrary, the word “comprise” and variations such as “comprises” or “comprising”, will be understood to imply the inclusion of stated elements but not the exclusion of any other elements.
[0044] Furthermore, unless otherwise mentioned, a singular form includes a plural meaning.
[0045] Figure 1 is a perspective view schematically showing a catalyst structure for preparing synthesis gas according to an embodiment. Figure 2 is perpendicular to Figure 1 2 is a cross-sectional view taken in the longitudinal direction of the flow path, and is an enlarged cross-sectional view showing the flow path in an enlarged manner.
[0046] In the following, reference is made to Figure 1 and Figure 2 , describing the structure of a catalyst for the preparation of synthesis gas.
[0047] The catalyst structure for preparing synthesis gas includes a substrate 2 and a catalytic material 14 arranged on the substrate 2 .
[0048] The substrate 2 includes flow paths 10 partitioned by partition walls 12 .
[0049] For example, the substrate 2 may have a honeycomb shape or a monolithic shape. Figure 1 and Figure 2 As shown, the substrate 2 may have a cylindrical shape, a cylindrical outer surface 4, an upstream end 6, and a downstream end 8 corresponding to the upstream end 6. The substrate 2 may have a plurality of thin parallel flow paths 10 formed inside.
[0050] like Figure 2 As shown, the flow path 10 is defined by partition walls 12 and extends in the longitudinal direction from the upstream end 6 to the downstream end 8. The partition walls 12 may be arranged so that the flow path 10 may have a generally regular cross-sectional shape, for example, a polygon such as a triangle, quadrilateral, hexagon, octagon, etc., a circle, or an ellipse.
[0051] The substrate 2 (e.g., the partition wall 12 of the substrate 2) may include a material having excellent heat transfer performance. For example, the material having excellent heat transfer performance may be a material having a thermal conductivity greater than or equal to about 10 W / mK. Examples of such materials may include silicon carbide (SiC), silicon nitride (Si 3 N 4 ), metal silicon (Si)-silicon carbide (SiC) composites, metal silicon (Si)-silicon nitride (Si 3 N 4 )complex or a combination thereof.
[0052] The catalyst structure including a material having excellent heat transfer performance can improve the heat transfer performance and thus reduce the temperature gradient in the catalyst layer to improve the performance of the catalyst, as well as reduce the pressure loss within the catalyst layer and the flow resistance of the reaction gas.
[0053] Therefore, the catalyst structure may have a thermal conductivity greater than or equal to 10 W / mK, for example, greater than or equal to 11 W / mK, greater than or equal to 12 W / mK, greater than or equal to 13 W / mK, greater than or equal to 14 W / mK, greater than or equal to 15 W / mK, greater than or equal to 16 W / mK, or greater than or equal to 17 W / mK; and less than or equal to 100 W / mK, for example, less than or equal to 90 W / mK, less than or equal to 80 W / mK, less than or equal to 70 W / mK, or less than or equal to 60 W / mK. When the catalyst structure has a thermal conductivity greater than or equal to 10 W / mK, the temperature gradient in the catalyst layer may be reduced, increasing the conversion rate of the reaction gas.
[0054] The partition wall 12 of the substrate 2 may be porous. In other words, the partition wall 12 of the substrate 2 may have a plurality of pores. The porosity of the partition wall 12 of the substrate 2 may be in the range of 10% to 80% or in the range of 20% to 70%. When the partition wall 12 of the substrate 2 has a porosity of less than 10%, the catalytic material may be coated in a smaller area and thus may not be well dispersed, but when the porosity is greater than 80%, the thermal conductivity of the catalyst structure may be reduced.
[0055] The catalytic material 14 is arranged on the surface of the partition wall 12 of the substrate 2. For example, the catalytic material 14 may be coated on the inner wall of the flow path 10 of the substrate 2. However, the flow path 10 is not closed by the coated catalytic material 14, but a fluid, for example, a reaction gas, may pass through.
[0056] The catalytic material 14 may be included in an amount within the range of 20 g to 300 g, within the range of 30 g to 300 g, within the range of 20 g to 250 g, or within the range of 30 g to 250 g per about 1 L volume of the catalyst structure. When the coating amount of the catalytic material 14 is less than 20 g per 1 L volume of the catalyst structure, the catalyst may be insufficient to convert the reaction gas, but when the coating amount is greater than 300 g per 1 L volume of the catalyst structure, the catalyst may act as a layer that interferes with heat conduction, adversely affecting performance.
[0057] The catalytic material 14 includes a metal oxide support and metal active particles supported on the metal oxide support.
[0058] For example, the metal oxide support may include alumina (Al 2 O 3 ), silicon dioxide (SiO 2 ), magnesium oxide (MgO), magnesium aluminate (MgAl 2 O 4 ), zirconium oxide (ZrO 2 ), cerium dioxide (CeO 2 ), lanthanum oxide (La 2 O 3 ), yttrium oxide (Y 2 O 3 ) or a combination thereof.
[0059] The metal active particles may include nickel (Ni), cobalt (Co), rhodium (Rh), ruthenium (Ru), iridium (Ir), palladium (Pd), platinum (Pt), gold (Au), iron (Fe), alloys thereof, or combinations thereof. These metals may be appropriately combined to improve carbon deposition, but among these metals, noble metals may be disadvantageous for economic feasibility.
[0060] Based on the total weight of the catalyst, the metal active particles may be included in an amount ranging from 5 wt% to 30 wt%, ranging from 5 wt% to 20 wt%, or ranging from 10 wt% to 20 wt%. When the metal active particles are used in an amount less than 5 wt%, the metal active particles may be insufficient to convert the reaction gas, deteriorating the catalyst performance. When the amount of the metal active particles is greater than 30 wt%, the metal active particles may be easily sintered during the reaction and carbon may be deposited, thereby deteriorating the performance and life of the catalyst due to the coke formation reaction and the particle aggregation phenomenon.
[0061] Herein, the metal active particles may include at least some oxides of the metal active particles. When the catalyst is prepared by drying and calcining after impregnating the precursor of the metal active particles in the metal oxide support, the metal active particles are partially reduced and oxidized, thereby generating oxides of the metal active particles in addition to the metal active particles on the catalyst surface.
[0062] Optionally, a metal oxide coating layer may be disposed on the surface of the metal oxide support. The metal oxide coating layer brings about a space confinement effect between the metal oxide support and the metal oxide coating layer to prevent the growth and aggregation of metal active particles during the synthesis gas reaction.
[0063] The metal oxide coating may include SiO 2 、Al 2 O 3 、MgO、MgAl 2 O 4 ,La 2 O 3 、CeO 2 、ZrO 2 , SiC, indium tin oxide (ITO), fluorine-doped tin oxide (FTO), or a combination thereof (e.g., SiO 2 or Al 2 O 3 ).
[0064] The metal oxide coating layer may be included in an amount ranging from 0.5 wt% to 10 wt%, ranging from 1 wt% to 8 wt%, ranging from 1 wt% to 7 wt%, or ranging from 1 wt% to 5 wt%, based on the total weight of the catalyst. When the metal oxide coating layer is included in an amount less than 0.5 wt%, since a coating effect is hardly obtained, the metal active particles may be sintered or gradually aggregated, and when the amount is included in an amount greater than 10 wt%, the content of the metal active particles may be reduced, and due to the thickness of the metal oxide coating layer, the material transfer resistance may be increased instead.
[0065] When metal active particles, which are active materials, are structurally well supported on a metal oxide support and are prevented from agglomerating by a metal oxide coating, the catalytic material can have durability against carbon deposition.
[0066] For example, a method of preparing such a catalytic material may include loading metal active particles on a porous metal oxide support and forming a metal oxide coating on the surface of the porous metal oxide support.
[0067] The supporting of the metal active particles can be performed by coating a metal active particle precursor solution on the porous metal oxide support and drying it and then calcining it.
[0068] Specifically, the metal active particle precursor solution can be prepared by adding a precursor of the metal active particles to a solvent. The precursor of the metal active particles can include nitrates, sulfates, acetates, chlorides, oxides, acetylacetonates, or combinations thereof of the metal active particles. The solvent can include distilled water, ethanol, methanol, ethylene glycol, propylene glycol, isopropanol, or combinations thereof.
[0069] Drying may be performed at a temperature ranging from 60° C. to 90° C. When the drying temperature is lower than 60° C., the metal active particles may leak out of the pores during calcination because the solvent is not completely removed. When the drying temperature is higher than 90° C., drying occurs so quickly that the metal active particles may leak out of the pores during drying.
[0070] The calcination may be performed at a temperature ranging from 400° C. to 1000° C. for 1 to 6 hours. When the calcination temperature is less than 400° C. or the calcination time is less than 1 hour, the precursor solution may not be converted into metal active particles. When the calcination temperature is greater than 1000° C. or the calcination time is greater than 6 hours, the metal active particles may be formed to be very large, thereby reducing the specific surface area of the catalyst.
[0071] On the other hand, the oxide of the metal active particles can be generated during the catalyst preparation process. For example, in the process of preparing a catalyst for preparing synthesis gas by bonding the metal active particles to a carrier, drying them, forming a metal oxide coating and calcining them, since the metal active particles are partially reduced and oxidized, in addition to the metal active particles on the surface, some oxides of the metal active particles may also be included on the surface of the carrier.
[0072] The formation of the metal oxide coating layer can be performed by mixing a support supporting metal active particles and a metal oxide precursor and calcining them.
[0073] For example, after the support carrying metal active particles is dispersed in a solvent, a surfactant (e.g., hexadecyltrimethylammonium bromide (CTAB)) is added thereto, and then ultrasonic treatment is performed to attach the surfactant to the surface of the support carrying metal active particles. Subsequently, a metal oxide precursor (e.g., aluminum isopropoxide) is injected therein, and then stirred for a coating reaction, and calcined to prepare a catalyst.
[0074] In this way, when a surfactant is used to form a metal oxide coating, the metal oxide coating may contain mesopores having a pore size in the range of 2 nm to 50 nm. If the metal oxide coating has mesopores with too large a pore size, the structural stability of the catalyst may be deteriorated, while if the mesopores have too small a pore size, the accessibility between the metal active particles and the reaction gas may be deteriorated.
[0075] The surfactant may include a nonionic, cationic or anionic surfactant in addition to cetyltrimethylammonium bromide, but the type thereof is not particularly limited.
[0076] The calcination may be performed at a temperature ranging from 400° C. to 1000° C. for 1 to 6 hours. When the calcination temperature is lower than 400° C. or the calcination time is less than about 1 hour, the surfactant may not be completely removed. When the calcination temperature is greater than 1000° C. or the calcination time is greater than 6 hours, the specific surface area of the catalyst may be greatly reduced.
[0077] For example, the prepared catalytic material may be coated on the inner wall of the flow path of the substrate.
[0078] In order to coat the catalytic material on the substrate, the prepared catalytic material can be first dispersed in an aqueous solution, and then a binder and an organic material are added thereto to prepare a slurry, which is then optionally ground by using a ball mill. In order to adjust the concentration of the slurry, the amount of the catalyst to be coated can be calculated as the mass of the catalyst to be coated / volume of the substrate. Subsequently, the slurry is coated on the substrate, and then dried and calcined to prepare a catalyst structure.
[0079] However, as described above, the method for preparing the catalyst structure is not limited to preparing the catalytic material in powder form, preparing it into a slurry, and coating the slurry on a substrate. Alternatively, the method may include coating a metal oxide support on a substrate, loading metal active particles thereon, and optionally forming a metal oxide coating. In some examples, the metal active particles may be directly loaded on the substrate, and optionally, a metal oxide coating may be formed thereon.
[0080] According to another exemplary embodiment, an apparatus for preparing synthesis gas includes the above-mentioned catalyst structure for preparing synthesis gas.
[0081] For example, the device for preparing synthesis gas includes a tubular reactor tube, and the catalyst structure can be filled in the reactor tube. Herein, the catalyst structure can be arranged so that the flow path of the catalyst structure can be arranged along the longitudinal direction of the reactor tube. Therefore, when the reaction gas is supplied to the reactor tube, the reaction gas can pass through the flow path of the catalyst structure.
[0082] Here, the catalyst structure may be in direct contact with the inner wall of the reactor tube to prevent channeling of the reaction gas when the reaction gas passes between the catalyst structure and the inner wall of the reactor tube. For example, the catalyst structure may have a diameter substantially equal to the inner diameter of the reactor tube. When the diameter of the catalyst structure is smaller than the inner diameter of the reactor tube, channeling of the reaction gas may occur, increasing non-reaction gas, thereby deteriorating catalyst performance.
[0083] In addition, a method for preparing synthesis gas according to another exemplary embodiment includes injecting a reaction gas and an oxidant into a flow path of a catalyst structure for preparing synthesis gas, and reforming the reaction gas through an endothermic reaction.
[0084] For example, a method for preparing synthesis gas is a method of adding carbon dioxide (a major greenhouse gas) to methane and steam (raw materials for conventional steam reforming) to convert them into synthesis gas, for example, combined steam and carbon dioxide reforming of methane represented by Reaction Formula 1 is performed to prepare synthesis gas including carbon monoxide and hydrogen.
[0085]
[0086] The reaction gas may include C1 to C20 alkanes, C1 to C20 alkenes, C1 to C20 alkynes, ammonia (NH 3 ), formaldehyde (HCOH), methanol (CH 3 OH) or a combination thereof.
[0087] The oxidant may include carbon dioxide (CO 2 ), steam (H 2 O), oxygen (O 2 ) or a combination thereof.
[0088] In some examples, the reaction gas may include methane, water, and carbon dioxide as an oxidant, and the synthesis gas may include hydrogen and carbon monoxide. For example, water may be included in the reaction gas in the form of steam.
[0089] The synthesis gas preparation method provides the reaction gas by adjusting the molar ratio of the reaction gas to obtain the synthesis gas having a desired composition.
[0090] The reaction gas may include methane and an oxidant (carbon dioxide and water) in a molar ratio ranging from 1:1 to 1:3 or in a molar ratio ranging from 1:1.2 to 1:2.
[0091] When the oxidant has a molar ratio of less than 1 (e.g., a ratio of 1:0.5), the conversion rate of methane may be reduced, and carbon deposition may increase, resulting in catalyst deactivation. When the molar ratio of the oxidant is greater than 3 (e.g., a ratio of 1:5), the conversion rate of carbon dioxide may be reduced, and less hydrogen may be produced due to less oxidation of the surface of the catalyst active material. When considering the conversion rate of the reaction gas, the H in the produced gas, 2 When adjusting the methane / CO ratio and carbon deposition, the molar ratio of methane to oxidant in the range of 1:1.2 to 1:2 may be optimal.
[0092] The oxidant may include carbon dioxide and water in a molar ratio ranging from 0.2:1.5 to 1.2:0.2. When water has a molar ratio greater than 1.5 (eg, 0.2:2), the catalyst may be deactivated due to unreacted residual steam.
[0093] On the other hand, in the case of hybrid reforming, in addition to methane, carbon dioxide and water, the reaction gas may further contain nitrogen. The molar ratio of the nitrogen contained relative to methane may be in the range of 1:1 to 1:3. Nitrogen may be used as a diluent to reduce the temperature fluctuation range of the catalyst layer during the reaction.
[0094] The reaction gas may be supplied at a space velocity in the range of 500 / h to 20000 / h or in the range of 1000 / h to 10000 / h. The supply rate of the reaction gas may be increased in proportion to the size of the hybrid reforming reactor and the capacity of the catalyst.
[0095] The reaction temperature and pressure of the hybrid reforming can be appropriately adjusted according to the composition of the desired synthesis gas. For example, the hybrid reforming reaction can have a temperature condition in the range of 600°C to 1000°C, in the range of 650°C to 900°C, or in the range of 800°C to 950°C. When the reaction temperature is lower than 600°C, the conversion rate of carbon dioxide can be significantly reduced, and a considerable amount of CO can be generated. 2 When the reaction temperature is higher than 1000°C, the heat energy is consumed inefficiently, resulting in thermal deactivation of the catalyst.
[0096] In addition, the pressure condition of the hybrid reforming reaction can be in the range of 0.5 atm to 20 atm, or in the range of 1 atm to 10 atm. When the reaction pressure is greater than 20 atm, the conversion rate of the reaction gas can be reduced, thereby changing the H 2 / CO ratio.
[0097] According to the method of preparing synthesis gas by using the catalyst, the conversion rate of methane and / or carbon dioxide into reaction gas may be in the range of 30 mol % to 99.9 mol %, which may be stable to carbon deposition at 900° C. for up to 100 hours.
[0098] Hereinafter, specific embodiments of the present disclosure are shown. However, the embodiments described below are only used to specifically illustrate or explain the present disclosure, and the scope of the present disclosure is not limited thereto.
[0099] Preparation Example: Preparation of Catalyst Structure
[0100] Example 1
[0101] (1) Loading nickel on metal oxide supports
[0102] Nickel was the active metal particle supported on a commercial alumina support. To load 12 wt% Ni on the alumina support, a solution of nickel nitrate hexahydrate (Ni(NO 3 ) 2 6H 2 O) was applied thereon, and then dried overnight in a convection oven at 80° C. The dried mixture was calcined at 800° C. for 2 hours (at a heating rate of 1° C. / min) in an air atmosphere.
[0103] (2) Formation of metal oxide coating
[0104] 1 g of the prepared catalyst was dispersed in 9 mL of ethanol by ultrasonication. Then, a solution prepared by dissolving 0.3 g of hexadecyltrimethylammonium bromide (Alfa-Aesar, 98%, hereinafter, CTAB) in 8 mL of ethanol and 0.6 mL of ammonia (NH 4 OH, Duksan Science, 25 to 30%), and then treated with ultrasound for an additional 10 minutes to allow CTAB to attach to the catalyst surface.
[0105] While vigorously stirring at room temperature, 0.1 mL of aluminum isopropoxide (AIP, Samchun Chemicals, 98%) was injected into it at 48 mL / h by a syringe pump, and then stirred for 5 hours to maintain the coating reaction. The product coated therewith was filtered, washed with ethanol, dried overnight at 80° C. in a conventional oven, and calcined at 550° C. for 2 hours in an air atmosphere to prepare a catalytic material.
[0106] (3) Coating the catalytic material on the substrate
[0107] The prepared catalytic material was dispersed in an aqueous solution, and a binder and an organic material were added thereto to make it in a slurry state, and then pulverized by using a ball mill. For the substrate, a honeycomb substrate including silicon carbide (SiC) was used, which had a thermal conductivity of 45 W / mK and a porosity of 42% of the partition wall. The concentration of the catalytic material was controlled to have a coating amount of 50 g / 1 L volume of the honeycomb carrier. Subsequently, the slurry of the catalytic material was coated on the honeycomb substrate, dried and calcined at 900°C to prepare a catalyst structure.
[0108] In addition, the apparatus for preparing synthesis gas may be constructed so that the prepared catalyst structure may contact the inner wall of a reactor tube having a diameter of 1 inch to prevent channeling of the reaction gas.
[0109] Example 2
[0110] A catalyst structure was prepared in the same manner as in Example 1, except that the coating amount of the catalytic material was changed to 20 g / 1 L volume of the substrate.
[0111] Example 3
[0112] A catalyst structure was prepared in the same manner as in Example 1, except that the coating amount of the catalytic material was changed to 100 g / 1 L volume of the substrate.
[0113] Example 4
[0114] A catalyst structure was prepared in the same manner as in Example 1, except that the coating amount of the catalytic material was changed to 250 g / 1 L volume of the substrate.
[0115] Example 5
[0116] A catalyst structure was prepared in the same manner as in Example 1, except that the amount of Ni supported on the carrier was changed to 20 wt %.
[0117] Example 6
[0118] A catalyst structure was prepared in the same manner as in Example 1, except that a honeycomb substrate having a thermal conductivity of 17 W / mK and a partition wall porosity of 60.5% was used.
[0119] Comparative Example 1
[0120] 12 wt% of Ni precursor of the catalyst active material was loaded on a commercial alumina support. After drying overnight in a conventional oven, the alumina precursor for overlay coating was melted and impregnated therein, and then calcined at 900 °C to prepare Ni-based Al 2 O 3Pellets (5×5 mm, thermal conductivity: 14 W / mK), then, an apparatus for preparing synthesis gas was configured by filling the pellets into a reactor tube to the same height to form a catalyst layer as in Example 1.
[0121] For reference, in Table 1, the Ni content of Example 1 is the Ni content of the catalytic material to be coated, and the content of Comparative Example 1 is the total Ni content of the pellet catalyst.
[0122] Comparative Example 2
[0123] A catalyst structure was prepared in the same manner as in Example 1, except that a cordierite substrate having a thermal conductivity of 2 W / mK and a partition wall porosity of 35% were used.
[0124] Comparative Example 3
[0125] A catalyst structure was prepared in the same manner as in Example 1, except that a FeCr alloy monolithic substrate having a thermal conductivity of 16 W / mK was used.
[0126] Example 7
[0127] The apparatus for preparing synthesis gas was manufactured in the same manner as in Example 1, except that the reactor tube had a larger inner diameter than the catalyst structure, so that the inner wall of the reactor tube could not contact the catalyst structure, but the catalyst structure could be supported by a mesh ring arranged at the bottom of the catalyst structure. In this context, the mesh ring was thick enough to slightly support the inner diameter of the reactor tube and the catalyst structure and prevent channeling of the reaction gas.
[0128] Example 8
[0129] An apparatus for preparing synthesis gas is manufactured in the same manner as in Example 1, except that the reactor tube has a larger inner diameter than the catalyst structure so that the catalyst structure may not contact the inner wall of the reactor tube, and the catalyst structure is surrounded by a ceramic pad so that the catalyst structure may be fixed within the reactor tube to prevent reaction gas channeling.
[0130] Example 9
[0131] An apparatus for preparing synthesis gas was manufactured in the same manner as Example 1, except that the reactor tube had a larger inner diameter than the catalyst structure so that the catalyst structure could not contact the inner wall of the reactor tube, thereby allowing reaction gas channeling.
[0132] Experimental Example 1: Measurement of the characteristics of the catalyst structure
[0133] (1) Measurement of thermal conductivity
[0134] Thermal conductivity is the amount of heat that moves through a unit area when there is a temperature difference of 1°C / unit length (thickness), and is a coefficient indicating the ease of heat transfer due to the temperature difference within the material. The unit is generally expressed as W / m·K, and the greater the thermal conductivity, the greater the heat transfer and the easier the heat transfer.
[0135] For example, the thermal conductivity of the honeycomb substrate can be measured by using a laser flash method. The laser flash method is performed by irradiating a laser on the surface of a sample to measure the heat from the rear surface of the sample and its time and deriving the specific heat (Cp) and thermal diffusivity (α) therefrom, which are used to calculate the thermal conductivity according to Equation 1.
[0136] The thermal conductivity of the substrates used in the preparation examples was measured, and the results are shown in Table 1.
[0137] [Equation 1] Thermal conductivity: λ = α·Cp·ρ (ρ: density)
[0138] (2) Composition analysis of catalytic materials
[0139] The composition of each catalytic material to be coated on the prepared catalyst structure was examined by X-ray fluorescence analysis (XRF) to measure the respective amounts of metal active particles and metal oxide supports, and the results are shown in Table 1.
[0140] Table 1
[0141]
[0142]
[0143] Experimental Example 2: Evaluation of reforming performance
[0144] Methane as a reaction gas was mixed with carbon dioxide and steam as an oxidant and reformed. The prepared catalyst structure was coated in a reactor tube and then heated to 900°C under a hydrogen atmosphere and reduced for 1 hour. Subsequently, CH 4 :CO 2 :H 2 O=1:0.5:1 was injected into the reactor. In this paper, the temperature was set at 900°C and the pressure was set at 1 bar. Figures 3 to 7 The reforming performance evaluation results are shown in FIG.
[0145] Figure 3 is a graph showing the results of evaluating the reforming performance of the catalyst structures prepared in Example 1 and Comparative Examples 1 to 3.
[0146] Reference Figure 3, the reforming performance according to the substrate type can be compared. Example 1 using the substrate with the highest thermal conductivity showed high conversion of methane and carbon dioxide. On the other hand, in addition to thermal conductivity, the reforming performance can be affected by the flow path according to the shape and size of the substrate or pellets, the material constituting the catalyst, etc.
[0147] Figure 4 Graph showing the results of evaluating the reforming performance of the catalyst structures prepared in Examples 1 and 6 and Comparative Example 3.
[0148] Reference Figure 4 , the reforming performance according to the thermal conductivity of the SiC substrate can be compared. Comparing the reforming performance evaluation results of Example 1 and Example 6, which use the same type of substrate material but exhibit different thermal conductivities, Example 6 exhibits a higher porosity than Example 1 and is therefore advantageous in dispersing the catalytic material, while Example 1 exhibits a higher thermal conductivity. Example 1 also exhibits a higher reforming performance than Example 6, which is not a large difference. Comparative Example 3 exhibits a similar thermal conductivity to Example 6, but there is a large difference in reforming performance. This confirms that the SiC substrate material plays an important role in reforming performance.
[0149] Figure 5 is a schematic diagram showing the results of evaluating the reforming performance of the catalyst structures prepared in Examples 1 to 4.
[0150] Reference Figure 5 , the reforming performance according to the coating amount of the catalytic material can be compared. Example 1 shows the highest methane and carbon dioxide conversion rate. Example 2 shows a low catalyst coating amount for processing the injected reaction gas, while Examples 3 and 4 show slightly deteriorated performance than Example 1, but still show high reforming performance.
[0151] Figure 6 is a schematic diagram showing the results of evaluating the reforming performance of the catalyst structures prepared in Examples 1 and 5.
[0152] Reference Figure 6 , the reforming performance according to the Ni content of the catalytic material can be compared. In Example 5, the Ni content was increased to improve the reforming performance of the catalyst structure, but there was no significant difference in the conversion rate of the reaction gas. However, only CO 2 The conversion rate dropped by about 3%. Therefore, the reforming performance is more affected by the substrate material than the Ni content.
[0153] Figure 7 is a schematic diagram showing the results of evaluating the reforming performance of the catalyst structures prepared in Example 1 and Examples 7 to 9.
[0154] Reference Figure 7, the reforming performance according to the reactor configuration can be compared. In Example 1, the catalyst structure is configured to contact the reactor tube by matching the diameter of the catalyst structure to the inner diameter of the reactor tube. Here, there is no channeling.
[0155] In Example 7, the apparatus was configured to use a catalyst structure having the same characteristics as the catalyst structure of Example 1 and a reactor tube having an inner diameter greater than the diameter of the catalyst structure. In Example 7, the gas layer between the catalyst structure and the inner wall of the reactor tube interfered with heat transfer and reduced reforming performance.
[0156] In Example 8, the apparatus was configured to use a catalyst structure having the same characteristics as the catalyst structure of Example 1, but the catalyst structure was externally wrapped with a ceramic mat to secure it to the inner wall of the reactor tube. In Example 8, the ceramic mat acted as a thermal insulator and reduced external heat transfer, thus deteriorating reforming performance.
[0157] Example 9 uses a catalyst structure having the same properties as Example 1, but the reactor tube has an inner diameter that is larger than the diameter of the catalyst structure. In addition, the apparatus of Example 9 is configured to allow channeling of the reaction gases. Compared to Example 7, in which channeling does not occur, Example 9 exhibits a degradation in catalyst performance.
[0158] While the present disclosure has been described in conjunction with what are presently considered to be practical exemplary embodiments, it is to be understood that the present disclosure is not limited to the disclosed embodiments, but is intended to cover various modifications and equivalent arrangements included within the spirit and scope of the appended claims.
Claims
1. A catalyst structure for preparing synthesis gas, the catalyst structure comprising: a substrate including flow paths separated by partition walls; as well as a catalytic material disposed on a surface of the partition wall of the substrate, The catalytic material comprises a metal oxide carrier and metal active particles supported on the metal oxide carrier, and The substrate includes silicon carbide (SiC), silicon nitride (Si3N4), a metal silicon (Si)-silicon carbide (SiC) composite, a metal silicon (Si)-silicon nitride (Si3N4) composite, or a combination thereof.
2. The catalyst structure according to claim 1, wherein the catalytic material is coated on the inner wall of the flow path of the substrate. The catalyst structure according to claim 1 , wherein the substrate has a honeycomb shape or a monolithic shape. The catalyst structure according to claim 1 , wherein the catalyst structure has a thermal conductivity of 10 W / mK or more. The catalyst structure according to claim 1 , wherein the partition wall of the substrate has a plurality of pores. 6 . The catalyst structure according to claim 5 , wherein the partition walls of the substrate have a porosity ranging from 10% to 80%.
7. The catalyst structure of claim 1, wherein the catalytic material is included in an amount ranging from 20 g to 300 g per 1 L volume of the catalyst structure.
8. The catalyst structure of claim 1, wherein the metal active particles comprise nickel (Ni), cobalt (Co), rhodium (Rh), ruthenium (Ru), iridium (Ir), palladium (Pd), platinum (Pt), gold (Au), iron (Fe), alloys thereof, or combinations thereof.
9. The catalyst structure of claim 1, wherein the metal oxide support comprises aluminum oxide (Al2O3), silicon dioxide (SiO2), magnesium oxide (MgO), magnesium aluminate (MgAl2O4), zirconium oxide (ZrO2), cerium dioxide (CeO2), lanthanum oxide (La2O3), yttrium oxide (Y2O3), or a combination thereof.
10. The catalyst structure of claim 1, wherein the metal active particles are included in an amount ranging from 5 wt% to 30 wt% based on the total weight of the catalytic material.
11. A device for preparing synthesis gas, the device comprising: a reactor tube comprising a catalyst structure for producing said synthesis gas, The catalyst structure comprises: (1) a substrate including flow paths separated by partition walls; and (2) a catalytic material disposed on a surface of the partition walls of the substrate, wherein the catalytic material comprises a metal oxide support and metal active particles supported on the metal oxide support, The substrate comprises silicon carbide (SiC), silicon nitride (Si3N4), metal silicon (Si)-silicon carbide (SiC) composite, metal silicon (Si)-silicon nitride (Si3N4) composite or a combination thereof, wherein the flow path of the substrate of the catalyst structure is arranged along the longitudinal direction of the reactor tube, and The reaction gas is configured to pass through the channel of the catalyst structure to generate the synthesis gas.
12. The apparatus of claim 11, wherein the catalyst structure is in direct contact with the inner wall of the reactor tube.
13. The apparatus according to claim 11, wherein the reaction gas is configured not to pass between the catalyst structure and the inner wall of the reactor tube.
14. A method for producing synthesis gas, the method comprising: injecting a reactant gas and an oxidant into a flow path of the catalyst structure; as well as reforming the reaction gas through an endothermic reaction to produce the synthesis gas, wherein the catalyst structure comprises a substrate having flow paths separated by partition walls, and a catalytic material disposed on a surface of the partition walls of the substrate, The catalytic material comprises a metal oxide carrier and metal active particles supported on the metal oxide carrier, and The substrate includes silicon carbide (SiC), silicon nitride (Si3N4), metal silicon (Si -Silicon carbide (SiC) composite, metal silicon (Si)-silicon nitride (Si3N4) composite or a combination thereof.
15. The method of claim 14, wherein the reaction gas comprises C1 to C20 alkanes, C1 to C20 alkenes, C1 to C20 alkynes, ammonia (NH3), formaldehyde (HCOH), methanol (CH3OH), or a combination thereof.
16. The method of claim 14, wherein the oxidant comprises carbon dioxide (CO2), steam (H2O), oxygen (O2), or a combination thereof.
Citation Information
Patent Citations
Fixed constant velocity joint
KR1020230111502A